Sanksi Adat Terhadap Pelaku Tindak Pidana Perzinaan di Desa Tangkit Kecamatan Sungai Gelam Kabupaten Muaro Jambi - Hidayat, Iman; Idrah, M. Chairul (Universitas Batanghari Jambi, 2024)
This research discusses customary sanctions against perpetrators of criminal acts of adultery in Tangkit Village, Sungai Gelam District, Muaro Jambi Regency. The formulation of the problem of this research is how the existence of customary sanctions in the criminal act of adultery through customary law in Tangkit Village, Sungai Gelam Subdistrict, Muaro Jambi Regency, what are the obstacles faced in resolving the criminal act of adultery through customary law in Tangkit Village, Sungai Gelam Subdistrict, Muaro Jambi Regency and what efforts are made to overcome the obstacles to the criminal act of adultery through customary law in Tangkit Village, Sungai Gelam Subdistrict, Muaro Jambi Regency. To analyse these problems, the approach used in research on customary sanctions against perpetrators of adultery in Tangkit Village, Sungai Gelam District, Muaro Jambi Regency as one of the sources of law is empirical, namely an approach to the problem studied by looking at the provisions contained in the applicable laws and regulations and then whether the regulations are applied properly or not in the implementation of law enforcement. To examine the three existing problems, the theory of criminal sanctions is used. The results of this study indicate that the form of settlement of adultery cases in Tangkit Village, Sungai Gelam Subdistrict, Muaro Jambi Regency is carried out in a way, namely: expulsion from the village / village but previously a village wash was held first, namely giving one buffalo, 100 bushels of rice, 50 coconuts and selemak semanis. Then the perpetrator apologised for his actions and signed the peace agreement on a stamp duty of RP. 6,000.00 (Surat Setih) in 8 (eight) copies to be forwarded to the Regent, local police, sub-district head, village head, customary chief, relatives and the person concerned. The customary decision must be implemented by the perpetrator with a maximum grace period of 3 months to implement it. When the sanctions have been imposed by the customary institution for adultery, but the perpetrator is unable to fulfil them, the customary institution obliges the extended family of each party to participate in the customary settlement. Problems encountered in the settlement of adultery cases in Tangkit Village, Sungai Gelam Sub-District, Muaro Jambi Regency, namely: There is a difference of opinion between the enforcement of customary punishment between the youth and the tengganai elders and adultery cases that are resolved by national criminal law, the legal process takes a long time and is expensive, causing a lot of suffering to the perpetrator. Efforts to overcome the problems that occurred included a personal approach from the youth and tengganai elders to continue to apply customary criminal law as the original law of the Indonesian people, by means of all parties deliberating in a traditional meeting to weigh the advantages and disadvantages of national criminal law and customary criminal law and finally in a traditional meeting decided to use customary criminal law in resolving this adultery case because the legal process was not long and the costs were also affordable and the approach of the customary institution of Tangkit Village, Sungai Gelam District, Muaro Jambi Regency. to the community to provide socialisation and education on the basis of Jambi Customary Law, namely Induk Undan Nan Lima, Pucuk undang nan eight and Anak undang nan twelve so that people know that customary criminal law still exists, applies, and has permanent legal force. The suggestion is that the Muaro Jambi Regency Government should provide and require every community to attend religious activities such as recitation and regular lectures so that the piety and faith of the community is strengthened rather than lust alone in order to avoid deviant behaviour and the customary institutions of Muaro Jambi Regency should be able to provide socialisation and counseling on the basis of Jambi Customary Law, namely Induk Undang Nan Lima, Pucuk undang nan eight and Anak undang nan twelve that customary criminal law can resolve adultery cases quickly, the legal process is not long, and the costs are affordable.